Effect of Preventive Chlamydia abortus Vaccination in Offspring Development in Sheep Challenged Experimentally - García-Seco, Teresa; Pérez-Sancho, Marta; Salinas, Jesús; Navarro, Alejandro; Díez-Guerrier, Alberto; García, Nerea; Pozo, Pilar; Goyache, Joaquín; Domínguez, Lucas; Álvarez, Julio (Frontiers in Veterinary Science, 2016)
Ovine enzootic abortion, caused by Chlamydia abortus, leads to important economic losses worldwide. In addition to reproductive failures, infection may impact lamb growth during the first weeks after birth, yet this effect has not been well characterized. Vaccination can help to control the disease but variable efficacy values have been described, possibly related with factors associated with the host, the vaccine, the parameter used for efficacy determination and the challenge conditions. In this context, we evaluated the efficacy of an inactivated standard commercial vaccine and a 1/2 diluted dose in pregnant sheep challenged with C. abortus by examining multiple indicators ofvaccine effect (including incidence of reproductive failures, bacterial excretion, and evolution of weight gain of viable lambs during the first month of life). Three groups of ewes [control non-vaccinated, C (n = 18); vaccinated with standard dose, SV (n = 16) and vaccinated with 1/2 dose, DV (n = 17)], were challenged approximately 90 days post-mating and tested using direct PCR (tissue samples and vaginal swabs) and ELISA (serum) until 31 days post-reproductive outcome. There were not significant differences in the proportions of reproductive failures or bacterial shedding after birth/abortion regardless the vaccination protocol. However, a beneficial effect of vaccination on offspring growth was detected in both vaccinated groups compared with the controls, with a mean increase in weight measured at 30 days of life of 1.5 and 2.5 Kg (p = 0.056) and an increase in the geometric mean of the daily gain of 8.4 and 9.7% in lambs born from DV and SV ewes compared to controls, respectively. Our results demonstrate the effect of an inactivated vaccine in the development of the offspring of C. abortus-infected ewes at a standard and a diluted dose, an interesting finding given the difficulty in achieving sufficient antigen concentration in the production of EAE-commercial vaccines.